PUSAT REHABILITASI DAN PENGEMBANGAN LANSIA DI KABUPATEN BANJAR - Mutiara Pangestu; Nurfansyah Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Elderly Rehabilitation and Development Center in Banjar Regency is an institution managed by the Social Service. This institution aims to protect, maintain, care for, and provide training for all elderly people, especially neglected and underprivileged elderly. The problem in this report was how to design elderly-friendly buildings with the availability of creative space and health support facilities in order to achieve prosperous, active, and productive elderly people. The method used in solving this problem was the Therapeutic Environment method. Based on observations, the concept of A Place to Reviving emerged to create a comfortable space for the elderly to spend their old age and slowly help restore the enthusiasm and level of productivity.